2000
DOI: 10.1007/pl00008361
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia in patients with triple A syndrome – a newly recognised finding

Abstract: Triple A syndrome is characterised by achalasia, alacrima, adrenal insufficiency and progressive neurological abnormalities including impaired autonomic nervous function. We present five patients with triple A syndrome in whom we describe xerostomia for the first time, a symptom which was presumed to be practically exclusive to Sjøgren syndrome and familial dysautonomia. Conclusion We recommend the investigation of salivation in all patients with triple A syndrome and treatment of xerostomia in order to ease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Xerostomia has been described in some case reports as a complaint among patients with 3A syndrome, and confirmatory sialometry has showed decreased salivary secretion 12,6467. Hyposalivation has also been identified as a cause of dysphagia after correction of achalasia 12.…”
Section: Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Xerostomia has been described in some case reports as a complaint among patients with 3A syndrome, and confirmatory sialometry has showed decreased salivary secretion 12,6467. Hyposalivation has also been identified as a cause of dysphagia after correction of achalasia 12.…”
Section: Oral Healthmentioning
confidence: 99%
“…Premature tooth loss has been described. In some cases this was attributed to decreased saliva production and subsequent tooth decay;64,65,69 however, there have been reports describing permanent tooth loss without an underlying gum, salivary, bone, or tooth pathology 59. Furthermore, gastroesophageal reflux, which is prevalent in patients with 3A, has been shown to contribute to tooth erosion 70…”
Section: Oral Healthmentioning
confidence: 99%
“…Osteoporosis, xerostomia, accommodative exotropia are examples of these disorders. 3,4 Babu et al 5 have evaluated the ocular manifestations of two affected siblings, and in addition to dry eyes, they have observed diminished pupillary light reflex. They have suggested that this was due to autonomic disregulation that could be seen in patients affected with the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The cornea of the eyes was not damaged, probably as a result of residual tear production. Xerostomia (described in 5 patients [12]) was absent.…”
Section: Resultsmentioning
confidence: 99%